The Conceptual Aspects of the Development of Recreational Areas and Environmental Protection Activities in the Context of European Integration - Drebot Oksana I.; Klym Nadiia M. (Bìznes Inform, 2025)
The occupation of the territories of Pryazovia and Crimea has caused negative changes in the development of certain occupied and adjacent territories; however, it has prompted the emergence of new ideas and directions for recreational development in the southern-central and western regions. The development of the recreational sector is of significant interest to both businesses and the State, especially concerning the moral-psychological recovery and rehabilitation of the population affected by combat operations, as well as military personnel involved in carrying out their duties. It is found that support for the industry’s development should occur not only at the national level but also at the level of local communities, with social awareness of common ecological problems and the needs of businesses among visitors to recreational areas. It is determined that the military actions initiated as a result of russia’s aggression have become the primary cause of the deterioration of recreational areas, as well as the irresponsible actions of the russian authorities pose a threat to the global environment. The direct financial losses to the ecosystem caused by the russian aggression over the years of conflict are only part of a larger problem, as their consequences leave a mark on the global ecosystem due to the movement of polluted air masses and the destruction of forest areas, water pollution, the effects of which will lead to global ecological issues in the future. The lack of safety at the Zaporizhzhia nuclear power plant could lead to a repeat of a global tragedy similar to the Chernobyl disaster. It is emphasized that in order to fully reveal the recreational potential of the regions, it is advisable for the government to develop and implement strategic measures for the financial support of business entities aimed at promoting its development, directing towards green technologies, and also to introduce an information policy to enhance the awareness of the population and, in fact, businesses regarding the need for a careful attitude towards the country’s ecology, its preservation, and protection.